Towards peptide-substituted titanocene anticancer drugs - Zagermann, Johannes; Deally, Anthony; Metzler-Nolte, Nils; Müller-Bunz, Helge; Wallis, Denise; Tacke, Matthias (Polyhedron, 2011)
An alkyne-substituted titanocene dichloride derivative was synthesised through the hydridolithiation reaction of an appropriately substituted fulvene. This titanocene dichloride derivative was then coupled with an azide-functionalised methylester-protected phenylalanine in a “click reaction” using a copper catalyst under anhydrous reaction conditions. [Display omitted] ► Alkyne-functionalisation of titanocene dichloride via substituted fulvene. ► Bulky substituents lead to rod-shaped titanocene structure in solid state. ► Successful [3+2]-cycloaddition with azide-functionalized phenylalanine. ► Experimental procedure not extendable to peptide enkephalin due to solubility issues. An alkyne-substituted fulvene was transformed via hydridolithiation followed by transmetallation with titanium tetrachloride into bis-[ p-(prop-2-ynyloxy)-benzyl-cyclopentadienyl] titanium(IV) dichloride. Single crystals of this titanocene derivative could be obtained and the structure determined by X-ray diffraction. It showed that this compound crystallises in the space group C2/c with four molecules in the monoclinic cell. The alkyne-substituted titanocene dichloride derivative was then subject to a copper-catalysed azide–alkyne cycloaddition with its azide-functionalised methylester-protected phenylalanine reaction partner in order to form a linking triazole. This reaction was performed under anhydrous conditions employing a dichloromethane/acetonitrile solvent mixture with copper(I) iodide and 2,6-lutidine as the catalyst system. Under these conditions the adduct between the protein mimic and the titanocene was formed without hydrolysing the titanium dichloride moiety.